Local government in England - Hasluck, E. L. (Publisher:University Press, 1948)
First published in 1936, this book by E. L. Hasluck provides a contemporary account of how local government functioned in England before the Second World War. This book will be valuable to political historians and those who wish to illuminate their understanding of contemporary local government by discovering its roots.